Patient Safety Incident Reporting in Sterile Processing: A Systems Perspective. (September 2022) - Segarra, Gabriel C.; Lusk, Connor; Catchpole, Ken; Rayo, Michael; Taaffe, Kevin; Fredendall, Lawrence; DeForest, Elise; Jeffries, Christine; Reynolds, Morgan
After use, surgical instruments are sent to a Sterile Processing Department (SPD) or facility to be cleaned, reorganized, maintained, sterilized and stored for eventual re-use. Though essential for safe, efficient and cost-effective surgical delivery, the functions, trade-offs and outcomes within SPDs have rarely been studied. Patient safety incident (PSI) reports are the most ubiquitous form of safety data collected within acute care environments and are often used to report issues in the SPD. Using the work systems analysis perspective we developed in previous work, we created a framework for areas where system failures might occur and manually evaluated PSI reports to investigate a period of possible system strain. We identify the assembly stage as a potentially significant contributor to system strain in the SPD and suggest that several issues related to sterile processing may be interconnected with an aim to assist decisionmakers and healthcare team members in SPD system management.